Medida da pressão arterial em crianças e adolescentes: recomendações das diretrizes de hipertensão arterial e prática médica atual - Souza, Maria Goretti Barbosa de [UNIFESP] (2009)
Rationale: There are pediatric consensus statements and guidelines recommendations to measure blood pressure of children and adolescents at every examination after age 3 years. Objective: To determine, in a school-based sample of children and adolescents, aged from 7 to 17 years, of both gender, in public and private schools, the frequency of students already submitted to blood pressure measure. Methods: A cross-sectional study was carried out, sampling from a population pool of elementary and middle schools, randomly selected. The sample was calculated based on the expected prevalence of hypertension for the age group. Data were collected through a questionnaire. Blood pressure was measured twice and hypertension was defined as mean systolic and/or diastolic blood pressure over the 95th percentile. Independent variables studied: sex; age groups; economic status; public/private school. Results: The final sample included 1253 students. The response rate was 97%: 1215 students; 531 males; mean age 12,4±3 years (236 from 7 to 9 years; 638 from 10 to 14 years; 341 from 15 to 17 years). Prevalence of hypertension was 7.7%; 348 students (29%) were already submitted to blood pressure measures (54% once; 35% 2 to 4 times; 11% 5 or more times). High economic status, private school and adolescent group were significantly associated to previous blood pressure measure. Conclusion: Despite of pediatric consensus statements and guidelines recommendations about importance of blood pressure measure at every examination after age 3 years, there is a very low frequency of this practice (29%) in children and adolescents.